Covid-19: an opportunity to reduce unnecessary healthcare. (14th July 2020) - Moynihan, Ray; Johansson, Minna; Maybee, Alies; Lang, Eddy; Légaré, France
Abstract : Recovering health systems can prioritise genuine need